Environmental health promotion at a National Science Festival: An experiential-education based approach. Issue 2 (2nd April 2020) - Duxbury, Theodore; Bradshaw, Karen; Khamanga, Sandile; Tandlich, Roman; Srinivas, Sunitha
Abstract: To increase individual and communal environmental health awareness through an experiential-education project. A computer-based pre- and postintervention quiz; an educational poster; an interactive board game; and a take-home information leaflet were utilized for a school learners-centered health promotion exhibit at a National Science Festival in Grahamstown, South Africa. Out of all the participants, 55.7% were female, and 76.5% attended or had attended a government school. Participants showed significant improvement in their pre- and posteducational intervention. The exhibit was effective in educating participants on environmental health, natural resources, and the impact environmental pollution has on their quality of life.